PERAN ORANG TUA DALAM MEMBINA AKHLAK ANAK USIA DINI DI ERA DIGITAL DI DESA KULATI KECAMATAN TOMIA TIMUR KABUPATEN WAKATOBI - Saputri, Wa Ode Elsya Sardilla; Susanti, Siti Misra; Henny, Henny (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to describe the role of parents in fostering moral character in early childhood during the digital era, focusing on Kulati Village, Tomia Timur District, Wakatobi Regency. The digital era presents new challenges for children’s moral education due to uncontrolled exposure to technology, which can influence their behavior and character. The problems identified in this study include the frequent use of impolite language by children, their inability to control anger, lack of understanding of manners towards adults, and weak parental supervision of gadget use. In addition, parents often fail to reinforce the moral values taught at school, further worsening the situation. This research employed a descriptive qualitative method, collecting data through observation, interviews, and documentation involving eight parents of early childhood children. The findings reveal that parents play four essential roles: as educators, motivators, role models, and companions. Parents strive to limit gadget use, provide positive examples, encourage good behavior, and build emotional closeness through open communication. However, limited time, low digital literacy, and work demands pose significant challenges in optimizing these roles. The study emphasizes the critical importance of active parental involvement in early moral education to shape children with strong character and noble values amid rapid technological advancement.